French women's writing, 1848-1994 - Holmes, Diana, 1949- (Women in context (London, England), 1996)
"A wide range of French women writers is surveyed, some like Sand, Colette, Beauvoir, Duras, already 'canonized', some marginalised or forgotten, some contemporary names not yet widely known outside France. These writers are seen within the political, economic and cultural context of women's lives and how these have changed across a century-and-a-half. Underpinning the whole account is the relationship between gender and language, between politics sexual and textual."--Jacket